Upaya Peningkatan Prestasi Santri Kelas IX Mata Pelajaran Fiqih Menggunakan Metode Card Sort di Pondok Pesantren Al-Islam Darul Falah Masaran Sragen - Abdurrosyid, Yusuf; Muslimin, Edy; Abbas, Ngatmin (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
This research aims to improve the academic achievement of ninth-grade students in Fiqh subject through the implementation of the Card Sort learning method at Al-Islam Darul Falah Islamic Boarding School Pilangbangu Sepat Masaran Sragen. The method used was Classroom Action Research conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data collection was carried out through observation, interviews, documentation, and learning outcome tests. The research subjects were 43 ninth-grade students. The Card Sort method was implemented by grouping students based on categories in Fiqh material, facilitating active discussions, and developing collaborative abilities. The results showed a significant improvement in student achievement, with the class average score increasing from 65.42 in pre-cycle to 75.86 in cycle I and 83.65 in cycle II. The percentage of learning completeness also increased from 27.91% in pre-cycle to 60.47% in cycle I and 83.72% in cycle II. The implications of this research indicate that the Card Sort method not only enhances cognitive aspects but also develops students' learning activities in various dimensions including active participation, group collaboration, categorization abilities, presentation skills, and questioning and answering capabilities. This method also creates a learning environment that engages students in constructing their own knowledge through various learning modalities.